The Concept of Emotional Stress, Its Theoretical and Conceptual Issues (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the essence of the concept of emotional stress and its psychological and sociological foundations. Factors influencing the formation of emotional stress and their manifestations in individual and social contexts are explained.The article also provides analytical insights on the interrelationship between stress and professional burnout in modern society, as well as their impact on human health and social activity. This article serves to develop a deeper understanding of emotional stress and strategies for its prevention.